Tuo-Min-Ding-Chuan Decoction Alleviate Ovalbumin-Induced Allergic Asthma by Inhibiting Mast Cell Degranulation and Down-Regulating the Differential Expression Proteins - Qin, Jingbo; Lv, Mingsheng; Jiang, Zeqiang; Meng, Xianghe; Wang, Yi; Cui, Jiarui; Wang, Ji; Wang, Qi (Frontiers in Pharmacology, 2021)
Allergic asthma is a stubborn chronic inflammatory disease, and is considered a co-result of many kinds of immune cells, especially mast cells, eosinophils and T lymphocytes. At present, the treatment methods of allergic asthma are limited and the side effects are obvious. Traditional Chinese medicine has been used to treat diseases for thousands of years in China. One such example is the treatment of allergic asthma, which take the characteristics of less adverse reactions and obvious curative effect. TuoMinDingChuan Decoction (TMDCD) is a traditional Chinese medicine compound for the treatment of allergic asthma optimized from MaXingGanShi Decoction (MXGSD), which put forward in Treatise on Febrile Diseases by Zhang Zhongjing in Eastern Han Dynasty. The compound shows a significant clinical effect, but the mechanism of its influence on the immune system is still unclear. The purpose of this study was to observe whether TMDCD could alleviate the symptoms of ovalbumin(OVA) challenged allergic asthma mice, and to explore its immune regulatory mechanism, especially on mast cell (MC) degranulation. The results showed TMDCD could not only reduce the airway hyperresponsiveness (AHR), inflammatory cell infiltration and mucus secretion in the lung tissue of OVA challenged mice, but also decrease the levels of total IgE, OVA specific IgE, histamine and LTC4 in serum. We found that TMDCD can down regulate the expression of Fractalkine, Tryptase ε, IL-25, CCL19, MCP-1, OX40L, Axl, CCL22, CD30, G-CSF, E-selectin, OPN, CCL5, P-selectin, Gas6, TSLP in OVA challenged mice serum by using mouse cytokine antibody array. These differential expression proteins were believed closely related to allergic asthma, and had direct or indirect relationship with MC activation and inflammation. The results of in vitro experiments showed that TMDCD inhibited the degranulation of RBL-2H3 cells stimulated by DNP-IgE/BSA. Taken together, we made the conclusion that TMDCD had anti-allergic and anti-asthmatic effects, and could regulate the differential expression proteins in serum of allergic asthma mice, which may be accomplished by inhibiting MC degranulation.